Breeding strategies of Dark-bellied Brent Geese Branta b. bernicla in a lemming-driven ecosystem in northern Siberia - Ebbinge, Bartwolt S.; Bom, Roeland; Broekhuizen , Sim; Cottaar, Fred; Kokorev, Yakov I.; Müskens, Gerard; Popov, Igor Y. (Wildfowl, 2025)
Long-term studies (1990–2008) of Dark-bellied Brent Geese Branta b. bernicla breeding on the Taimyr Peninsula in the Russian high Arctic, revealed a three-year cycle in breeding success linked to Siberian Lemming Lemmus sibiricus and Collared Lemming Dicrostonyx torquatus dynamics. Peak lemming years provide abundant prey for Snowy Owls Nyctea scandiaca, Arctic Foxes Vulpes lagopus and Pomarine Skuas Stercorarius pomarinus, whose interactions coincidently facilitate Brent Goose nesting. Snowy Owls defend their own territories against Arctic Foxes, and Pomarine Skuas do the same against both Arctic Foxes and Snowy Owls, severely restricting foxes and owls from preying upon Brent Geese, their nests and their goslings. Brent clutch size varied from an average of five eggs in Snowy Owl territories, to four eggs in gull Larus sp. colonies in peak lemming years, and three eggs in gull colonies in non-lemming years. Following lemming crashes (for reasons not understood), predator abundance remains high and Brent completely fail to breed or skip reproduction, as foxes and owls switch to alternative prey and skuas are absent from the area. In the third year, with predator decline (through starvation or emigration) and lemming recovery, Brent Goose nesting success improves. A year later, the three-year cycle starts again. The key role of skuas in limiting the owls’ ability to catch and carry larger prey, such as geese, creates fox-free areas where Brent are able to nest successfully, confirming their previously overlooked role in the interspecific predator-prey interactions shaping Brent Goose reproductive success in the high Arctic. This review of papers and reports from the long-term studies describes how complex predator-prey and interspecific interactions determine the annual variation in breeding outcomes for Dark-bellied Brent Geese.